Relationship between muscle fiber pennation and force generation capability in Olympic athletes - Ichinose, Y.; Kanehisa, H.; Ito, M.; Kawakami, Y.; Fukunaga, T. (International Journal of Sports Medicine, 1998)
The thickness (TBmt) and fiber pennation angle (TBpen) of triceps brachii as well as isokinetic force developed during elbow extension were measured in Olympic athletes to investigate the relationship between muscle fiber pennation and force generation capability. The subjects were male members of the 1996 Japanese Olympic team who competed in seven different events; 9 wrestlers, 16 soccer players, 11 sprinters, 5 judo athletes, 7 gymnasts, 9 rowers and 18 baseball players. The TBmt and TBpen, measured by a B-mode ultrasound, ranged between 29 mm and 50 mm and between 11 degrees and 30 degrees, respectively, and on average were larger in the judo athletes, wrestlers and gymnasts compared to the other groups. A significant correlation (r=0.580, p < 0.05) was found between TPpen and TBmt per unit of the upper arm length, and so the observed event-related differences in TBpen tended to reflect the differences in TBmt. The isokinetic forces relative to the cross-sectional area (CSA) estimated from TBmt, measured at two constant velocities of 1.05 rad/s (F1.05/CSA) and 3.14 rad/s (F3.14/ CSA), were negatively correlated to the CSA; r=-0.617 (p < 0.05) for F1.05/CSA and r=-0.635 (p < 0.05) for F3.14/CSA. In addition, low but significant negative correlations existed between TBpen and both F1.05/CSA (r=-0.365, p < 0.05) and F3.14/ CSA (r=-0.336, p <0.05). Even when the effect of TBpen was statistically normalized, the F1.05/CSA and F3.14/CSA were still negatively correlated to the CSA, r=-0.530 (p < 0.05) for F1.05/ CSA and r=-0.561 (p < 0.05) for F3.14/CSA. Therefore, at least in the Olympic athletes tested in this study, the magnitude of the pennation angles reflects muscle size, but it does not seem to be a factor that explains extensively the lower F/CSA in athletes with large muscle size.